Treatment Induced Cytotoxic T-Cell Modulation in Multiple Myeloma Patients - Barilà, Gregorio; Pavan, Laura; Vedovato, Susanna; Berno, Tamara; Lo Schirico, Mariella; Arangio Febbo, Massimiliano; Teramo, Antonella; Calabretto, Giulia; Vicenzetto, Cristina; Gasparini, Vanessa Rebecca; Fregnani, Anna; Manni, Sabrina; et al. (Frontiers in Oncology, 2021)
The biology of plasma cell dyscrasias (PCD) involves both genetic and immune-related factors. Since genetic lesions are necessary but not sufficient for Multiple Myeloma (MM) evolution, several authors hypothesized that immune dysfunction involving both B and T cell counterparts plays a key role in the pathogenesis of the disease. The aim of this study is to evaluate the impact of cornerstone treatments for Multiple Myeloma into immune system shaping. A large series of 976 bone marrow samples from 735 patients affected by PCD was studied by flow analysis to identify discrete immune subsets. Treated MM samples displayed a reduction of CD4+ cells (p<0.0001) and an increase of CD8+ (p<0.0001), CD8+/DR+ (p<0.0001) and CD3+/CD57+ (p<0.0001) cells. Although these findings were to some extent demonstrated also following bortezomib treatment, a more pronounced cytotoxic polarization was shown after exposure to autologous stem cell transplantation (ASCT) and Lenalidomide (Len) treatment. As a matter of fact, samples of patients who received ASCT (n=110) and Len (n=118) were characterized, towards untreated patients (n=138 and n=130, respectively), by higher levels of CD8+ (p<0.0001 and p<0.0001, respectively), CD8+/DR+ (p=0.0252 and p=0.0001, respectively) and CD3+/CD57+ cells (p<0.0001 and p=0.0006, respectively) and lower levels of CD4+ lymphocytes (p<0.0001 and p=0.0005, respectively). We demonstrated that active MM patients are characterized by a relevant T cell modulation and that most of these changes are therapy-related. Current Myeloma treatments, notably ASCT and Len treatments, polarize immune system towards a dominant cytotoxic response, likely contributing to the anti-Myeloma effect of these regimens.